Giant Cell Arteritis - Ness, Thomas; Nölle, Bernhard (Klinische Monatsblätter für Augenheilkunde, 2024)
Giant cell arteritis (GCA) is the most common primary vasculitis and is associated with potential bilateral blindness. Neither clinical nor laboratory evidence is simple and unequivocal for this disease, which usually requires rapid and reliable diagnosis and therapy. The ophthalmologist should consider GCA with the following ocular symptoms: visual loss or visual field defects, transient visual disturbances (amaurosis fugax), diplopia, eye pain, or new onset head or jaw claudication. An immediate ophthalmological examination with slit lamp, ophthalmoscopy, and visual field, as well as color duplex ultrasound of the temporal artery should be performed. If there is sufficient clinical suspicion of GCA, corticosteroid therapy should be initiated immediately, with prompt referral to a rheumatologist/internist and, if necessary, temporal artery biopsy should be arranged. Numerous developments in modern imaging with colour duplex ultrasonography, MRI, and PET-CT have the potential to compete with the classical, well-established biopsy of a temporal artery. Early determination of ESR and CRP may support RZA diagnosis. Therapeutically, steroid-sparing immunosuppression with IL-6 blockade or methotrexate can be considered. These developments have led to a revision of both the classification criteria and the diagnostic and therapeutic recommendations of the American College of Rheumatologists and the European League against Rheumatism, which are summarised here for ophthalmology.
Keywords: giant cell arteritis; AION; duplex ultrasound; EULAR; MRI